Leading through performance crises: soccer coaches’ insights on their strategies—a qualitative study - Rausch, Constantin; Fritsch, Julian; Altmann, Stefan; Steindorf, Lena; Spielmann, Jan; Jekauc, Darko (Frontiers in Psychology, 2025)
IntroductionPerformance crises in sports are recognized as particularly stressful environments, where coaches are held responsible to a large extent for winning matches. During these challenging times, coaches play a crucial role, as their behaviors can significantly impact the course of a crisis, either improving or exacerbating the situation. Therefore, the aim of the current study was to explore the various roles professional soccer coaches adopt during a performance crisis in order to manage them.MethodsSixteen semi-structured interviews were conducted with professional soccer coaches aged between 32 to 54 years (M = 43.81, SD = 6.46), with coaching experience ranging from 7 to 23 years (M = 15.44, SD = 5.0). The qualifications of the participants included eleven UEFA Pro Licenses, two UEFA A Licenses, one UEFA Goalkeeping A License, and two coaches without a UEFA License. Using an inductive reflexive thematic analysis within a broader deductive framework, two fundamental roles (i.e., Self-Manager, People-Manager) and three soccer-specific roles (i.e., the Soccer Expert, the Psychologist, the Administrator) were identified.ResultsThe roles of the Self-Manager and People-Manager are essential for coaches to understand, regulate, and influence themselves and others, enabling them to effectively perform the specific behaviors associated with each soccer-specific role. The Soccer Expert encompasses soccer-specific knowledge and expertise, the Psychologist focuses on addressing the psychological needs of both individual players and the entire team, and the Administrator is characterized by overseeing the administrative and organizational elements.DiscussionEmphasizing the interpersonal dimension of coaching, advanced self-management and communication competencies are particularly highlighted. Overall, by exploring coaches’ experiences, this study may contribute to the growing body of literature on crisis management in sports and offers practical implications for coaches to support themselves and their players during performance crises.